2017
DOI: 10.1136/jmedgenet-2016-104435
|View full text |Cite
|
Sign up to set email alerts
|

PBX1haploinsufficiency leads to syndromic congenital anomalies of the kidney and urinary tract (CAKUT) in humans

Abstract: Our results indicate that haploinsufficiency leads to syndromic CAKUT as supported by the-null mice model. Correct PBX1 dosage appears to be critical for normal nephrogenesis and seems important for brain development in humans. CMA should be recommended in cases of fetal renal anomalies to improve genetic counselling and pregnancy management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
67
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(69 citation statements)
references
References 45 publications
1
67
0
Order By: Relevance
“…Genital abnormalities are commonly reported in male patients with PBX1 mutations (10/14), with the phenotypic spectrum ranging from cryptorchidism to partial development of female internal and/or external genitalia (Alankarage et al, ; Eozenou et al, ; Kia et al, ; Riedhammer et al, ; Slavotinek et al, ; Le Tanno et al, ). Interestingly, the second affected sibling (II‐5; 46, XY) presented here showed complete sex reversal of both internal and external organs, without any signs of male gonad development (no streak gonad).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Genital abnormalities are commonly reported in male patients with PBX1 mutations (10/14), with the phenotypic spectrum ranging from cryptorchidism to partial development of female internal and/or external genitalia (Alankarage et al, ; Eozenou et al, ; Kia et al, ; Riedhammer et al, ; Slavotinek et al, ; Le Tanno et al, ). Interestingly, the second affected sibling (II‐5; 46, XY) presented here showed complete sex reversal of both internal and external organs, without any signs of male gonad development (no streak gonad).…”
Section: Discussionmentioning
confidence: 99%
“…De novo mutations in PBX1 were first identified as a cause of CAKUT in humans in 2017 (MIM: 617641) following earlier work demonstrating renal hypoplasia, renal ectopia, and renal agenesis in a Pbx1 −/− mouse model (Heidet et al, ; Le Tanno et al, ; Schnabel, Selleri, & Cleary, ; Slavotinek et al, ). The reported heterozygous disease causing mutations in PBX1 include partial and complete gene deletions, truncating, splice site and missense variants (Figure S1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chromosomal rearrangements encompassing PBX1 , t(1;19)(q23;p13.3), are associated with lymphoblastic leukemia (Williams et al, ). Recently, mutations involving the human PBX1 gene have been described as a cause of congenital anomalies of the kidney and urinary tract (CAKUT; Heidet et al, ; Le Tanno et al, ). In this study, we identified a specific de novo PBX1 missense mutation in the highly conserved TALE homodomain associated with a lack of testis‐determination.…”
mentioning
confidence: 99%
“…Congenital anomalies of the kidney and urinary tract (CAKUTs) occur in 3–6 per 1000 live births, accounting for most cases of paediatric end-stage kidney disease 1 . However, the molecular basis of CAKUT and anomalies of the external genitalia is poorly understood.…”
mentioning
confidence: 99%